Dielectrophoretic K562 cell entrapment device using benchtop microfluidics fabrication - Wee, Wei Hong; Razak, Mohd Azhar Abdul; Kadri, Nahrizul Adib (American Scientific Publishers, 2012)
A microfluidics-based device that has the capability to trap cells has been designed and constructed and its capabilities have been demonstrated using dielectrophoresis-a promising tool for the selective manipulation and separation of cells, bacteria and other bioparticles. The device consists of a dielectrophoretic chamber and an interdigitated electrode geometry that is fabricated from gold-coated glass slides. It was designed with the intention of providing a device that was compatible with standard laboratory equipment and had the capability to prevent leakage and discriminate cells. Experimental results reveal that the device is capable of trapping leukemic K562 cells at an average efficiency of 94.2. In addition to this, the design offers a number of advantages, which include the ability to exchange microscope slides and change separation chamber height. It is also reusable, easy to assembly and cleaning and provides a simple method of connecting electrodes and a power source. The device has the potential to become very beneficial in the preliminary stages of many diagnostic and immunosensing applications that require separation of different types of cells. Â© 2012 American Scientific Publishers All rights reserved.